2010
DOI: 10.1086/656329
|View full text |Cite
|
Sign up to set email alerts
|

Atmosphere Extinction at the ORM on La Palma: A 20 yr Statistical Database Gathered at the Carlsberg Meridian Telescope

Abstract: The Observatorio del Roque de los Muchachos (ORM), in the Canary Islands (Spain), was one of the candidates to host the future European Extremely Large Telescope (E-ELT) and is the site of the Gran Telescopio Canarias (GTC), the largest optical infrared facility to date. Sky transparency is a key parameter as it defines the quality of the photometry to be acquired in the astronomical observations. We present a study of the atmosphere extinction at the ORM, carried out after analysis of a database spanning more… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 21 publications
4
15
0
Order By: Relevance
“…This leads to typical Ångström exponents of 1.5-2.0 [26,30] and a single scattering albedo of 0.91 [27] and LIDAR ratios around 30 sr [31]. These findings are compatible with the median value for the V-band extinction of 0.13 mag airmass −1 found by [8], translating into an AOT of about 0.02.…”
Section: Aerosol Profilessupporting
confidence: 66%
See 3 more Smart Citations
“…This leads to typical Ångström exponents of 1.5-2.0 [26,30] and a single scattering albedo of 0.91 [27] and LIDAR ratios around 30 sr [31]. These findings are compatible with the median value for the V-band extinction of 0.13 mag airmass −1 found by [8], translating into an AOT of about 0.02.…”
Section: Aerosol Profilessupporting
confidence: 66%
“…Aerosols have been characterized at the ORM with the help of elastic LIDARs [10,23], dust counters [6] and extinction measurements by optical telescopes [8]. Moreover, several types of particulate analyzers and nephelometers are employed at the Izaña station on Tenerife [25][26][27] and on airplanes [28].…”
Section: Aerosol Profilesmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also a hint of the tail-end of effects from the El Chichón eruption in Mexico in 1982 April where the start of the data in 1984 show extinction values around 0.1, double the typical value expected outside of a dust intrusion. Both Guerrero et al (1998) and García-Gil et al (2010) have previously observed these features from telescopes based at the Canary Islands.…”
Section: Deriving Extinction Coefficientsmentioning
confidence: 84%